Diels–Alder adducts of a labdane diterpenoid from the Chinese liverwort Pallavicinia subciliata - Shu-Gong, Liu; Chun-Yang, Zhang; Jin-Chuan Zhou; Jing-Jing, Han; Ming-Zhu, Zhu; Jiao-Zhen Zhang; Li, Yi; Ze-Jun Xu; Meng, Hui; Wang, Xue; Zong, Yan; Shuang-Zhi Yuan; et al. (Organic chemistry frontiers an international journal of organic chemistry, 2022)
A 7,8-seco-2,8-cyclolabdane diterpenoid, pallasubcin A (1), and three rare pallasubcin A-derived dimers, pallasubcins B–D (2–4), formed via a Diels–Alder reaction between C-12–C-14′ and C-15–C-15′ were isolated from the Chinese liverwort Pallavicinia subciliata. Their structures were elucidated by comprehensive spectroscopic analysis, X-ray single crystal diffraction, and ECD calculations. Plausible biogenetic pathways are presented for all compounds. Preliminary anti-inflammatory determinations showed that compound 2 exhibited strong activity under nontoxic concentrations with a 73.03% (25 μM) maximum inhibition rate of NO production on LPS-induced RAW 264.7 murine macrophages.